Some of the Properties of Binderless Particleboard Manufactured from Bamboo - Ragil Widyorini; Ari Puspa Yudha; Tibertus Agus Prayitno (Wood Research Journal, 2011)
Bambo particles as a waste byproduct from bamboo processing industry are suggested to be a promising material for binderless particleboard. The quality of binderless particleboard is affected by several factors, such as pretreatment, pressing method, pressing condition, moisture content, and particle size. This study was focused on the effect of particle size and moisture content on the physical and mechanical properties of binderless particleboard from Petung bamboo (Dendrocalamus asper Backer) and conducted using the completely randomized design with two factors. Bamboo particles in three types of particle size, i.e. coarse (10~20 mesh), medium (20~60 mesh), and fine (passed 60 mesh), were used as materials for binderless board. Each particle size was then prepared for two moisture content conditions: air dry and 20±2%. Binderless boards were prepared by hot pressing at temperature of 200°C for 15 min, and the properties of the binderless boards were then evaluated according to the Japanese Industrial Standard for particleboard, JIS A 5908. The results showed that the binderless boards made from 20±2% moisture content particles showed better mechanical and dimensional properties than those made from air-dried particles. The binderless particleboard made from medium size and the moisture content of 20±2% recorded a modulus of rupture of 94 kg/cm², water absorption of 29%, thickness swelling of 5%, internal bond strength of 2.7 kg/cm², and modulus of elasticity of 19.490 kg/cm².